Ecomotricidade do plantar e do cuidar: um projeto ecopedagógico para a educação infantil - Silva, Tamires Cruz Santos (2023)
The urban-capitalist-western way of life brings us many benefits, such as easy access to medical care, formal education, science, and cultural diversity. At the same time, this predominant way of living and being in the world results in social and environmental problems that cannot be solved in time, especially the ones associated with inequalities that cause poverty and the unsustainable exploitation of natural resources. Before this reality, much has been discussed in recent decades about the need to overcome anthropocentric and capitalocentric paradigms, aiming for a social structure in which the balance of ecological systems prevails, including the right to life for all living beings on the planet. Educational methodologies focused on merely intellectually nurturing people have proven insufficient to encourage this paradigm shift that gradually moves us away from the current context of imminent destruction of the biosphere and extinction of human life and that brings us closer to an active movement to (re)take an ecological cosmovision (ecosomaesthetic-environmentally ethical-ecopolitical). In this sense, this work has the general objective of evaluating how the Ecomotricity of Planting and Caring (EPC), aligned with social and environmental aspects (always involving cultural and socioeconomic aspects) of Food and Nutrition Security (FNS), can be used as an ecopedagogical project to school contexts. As specific objectives: (1) to develop the conceptual, methodological and eco-pedagogical structures of the EPC; (2) analyze how the conceptual and empirical field of FNS contributes to the structure (conceptual, methodological, ecopedagogical) of EPC; and (3) elaborate, based on the structures developed in this study, a proposal for the insertion of EPC as a praxis in school contexts, specifically in early childhood education. To guide this interweaving of themes, we used the methodology of bibliographic review allied to the dialectical method to organize this research of a basic, theoretical, and exploratory nature. We presented this practical framework to be generative as an ecopedagogical methodology for school contexts in which horizontal relationships are developed between different school actors for the construction of vegetable gardens in the school environment. From the perspective of the EPC, the gardens are educational and educators, showing the relational, affective, and interactive complexity between human and non-human beings. From the construction of the vegetable gardens, we project the transformation of the project into a process, in the construction of knowledge based on praxis (research + planting/caring) that involves the entire school community through the action of the teacherresearcher.